(untitled) (International Journal of Innovative Technologies in Economy, 2018)
This article is about analyzing and decentralization strategy in Eastern Georgia. An ongoing process of decentralization puts on the agenda the regional infrastructure planning, development and optimization. The political importance is given to the creation of the regional infrastructure development strategy. Prior to that, it is important to note the existing regional infrastructure. It is not only about traditionally the highland regions, but the general municipalities, development potentials and perspectives. The above mentioned is particularly relevant to find that all municipalities have their own niche, that is attractive to the tourists and will be able to develop as well as maintain population in rural areas.